Iron-Restricted Diet Affects Brain Ferritin Levels, Dopamine Metabolism and Cellular Prion Protein in a Region-Specific Manner - Pino, Jessica M. V.; da Luz, Marcio H. M.; Antunes, Hanna K. M.; Giampá, Sara Q. de Campos; Martins, Vilma R.; Lee, Kil S. (Frontiers in Molecular Neuroscience, 2017)
Iron is an essential micronutrient for several physiological functions, including the regulation of dopaminergic neurotransmission. On the other hand, both iron and dopamine can affect the folding and aggregation of proteins related with neurodegenerative diseases, such as cellular prion protein (PrPC) and α-synuclein, suggesting that deregulation of iron homeostasis and the consequential disturbance of dopamine metabolism can be a risk factor for conformational diseases. These proteins, in turn, are known to participate in the regulation of iron and dopamine metabolism. In this study, we evaluated the effects of dietary iron restriction on brain ferritin levels, dopamine metabolism and the expression levels of PrPC and α-synuclein. To achieve this goal, C57BL/6 mice were fed with iron restricted diet (IR) or with normal diet (CTL) for one month. IR reduced iron and ferritin levels in liver. Ferritin reduction was also observed in the hippocampus. However, in the striatum of IR group, ferritin level was increased, suggesting that under iron-deficient condition, each brain area might acquire distinct capacity to store iron. Increased lipid peroxidation was observed only in hippocampus of IR group, where ferritin level was reduced. IR also generated discrete results regarding dopamine metabolism of distinct brain regions: in striatum, the level of dopamine metabolites (DOPAC and HVA) was reduced; in prefrontal cortex, only HVA was increased along with the enhanced MAO-A activity; in hippocampus, no alterations were observed. PrPC levels were increased only in the striatum of IR group, where ferritin level was also increased. PrPC is known to play roles in iron uptake. Thus, the increase of PrPC in striatum of IR group might be related to the increased ferritin level. α-synuclein was not altered in any regions. Abnormal accumulation of ferritin, increased MAO-A activity or lipid peroxidation are molecular features observed in several neurological disorders. Our findings show that nutritional iron deficiency produces these molecular alterations in a region-specific manner and provide new insight into the variety of molecular pathways that can lead to distinct neurological symptoms upon iron deficiency. Thus, adequate iron supplementation is essential for brain health and prevention of neurological diseases.